Exile in Mid-Qing China : banishment to Xinjiang, 1758-1820 - Waley-Cohen, Joanna (Yale historical publications (Unnumbered), 1991)
"Banishment to Xinjiang ranked second in severity only to death in Qing law. Intimidated immediately upon the addition of that Central Asian frontier to the Chinese empire, it at once became a vital element of both the legal system and the project of colonizing the new frontier. In this book Joanna Waley-Cohen traces the establishment and initial years of the system, showing how the Qing government really worked in the decades before dynastic decline took firm hold, exploring the role of banishment in Chinese mainstream and frontier society, and evaluating the system in the context of state expansion, political conflict, and the criminal justice system. Based on archival and published government documents, biographies, and contemporary accounts, the book addresses such topics as the varied crimes and social origins of the Xinjiang exiles, the logistics of the several months' journey into exile, the role of exiles in the colonization of the new frontier, the experiences of both banished officials and ordinary convicts, the exiles' prospects for release and return, the literature of Xinjiang banishment, and the self-perception of exiled scholars as the heirs to a long tradition. The author demonstrates that the intended use of convicts as colonists was only moderately successful, but the influence of temporarily banished government officials was unexpectedly important in that it ultimately contributed to the political integration of Xinjiang into the empire."--Publisher description